The “Cek Khodam” Phenomenon on Tiktok In Online Media Discourse: An Islamic Legal Perspective - Qudratullah Qudratullah; Putri Diesy Fitriani; Mizanurafi’ Ghifarhadi Prasiefa; Syamsinar Syamsinar; Mohammad Harith Amlus (Universitas Muhammadiyah Bandung, 2025)
This study examines the “Cek Khodam” phenomenon on TikTok by analyzing its construction in online media discourse and its implications from an Islamic legal perspective. Existing studies on digital culture tend to emphasize virality and user engagement, while limited attention has been given to how mystical digital content is framed in the media and evaluated through Islamic jurisprudence, indicating a significant research gap. This research employs a qualitative approach using library research, with data drawn from online news articles published in Indonesian media during June–July 2024. The study applies Robert N. Entman’s framing model to explore how the phenomenon is defined, interpreted, and morally evaluated in digital narratives. The findings reveal that “Cek Khodam” is framed as both entertainment and controversy, reflecting the commodification of spiritual beliefs in digital culture. From an Islamic legal perspective, the phenomenon raises concerns related to gharar, deception, and unverifiable spiritual claims. These practices can be critically examined through sadd al-dharī‘ah and contradict the objectives of maqāṣid al-sharī‘ah, particularly in preserving intellect and faith. This study contributes by integrating media framing analysis with ushul fiqh, offering a novel framework for regulating digital religious content.